2021
DOI: 10.1111/iar.12422
|View full text |Cite
|
Sign up to set email alerts
|

Great earthquake at 7.3 ka inferred from tsunami deposits in the Sukumo Bay area, Southwestern Japan

Abstract: Tsunami deposits in Kyushu Island, Southwestern Japan, have been attributed to the 7.3 ka Kikai caldera eruption, but their origin has not been confirmed. We analyzed an 83-cm-thick Holocene event deposit in the SKM core, obtained from incised valley fill in the coastal lowlands near Sukumo Bay, Southwestern Shikoku Island. We confirmed that the event deposit contains K-Ah volcanic ash from the 7.3 ka eruption. The base of the event deposit erodes the underlying inner-bay mud, and the deposit contains material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…A fragment of Cyphastrea sp. with an age of 7.0 ka was found in a Holocene sediment core from Sukumo Bay in Kochi Prefecture (32.9°N) (Nanayama et al 2021). A colony of D. speciosa indicates that initiation of formation of the Numa coral bed in Chiba Prefecture dates back to 7.8 ka (Sato et al 1968).…”
Section: Resultsmentioning
confidence: 96%
“…A fragment of Cyphastrea sp. with an age of 7.0 ka was found in a Holocene sediment core from Sukumo Bay in Kochi Prefecture (32.9°N) (Nanayama et al 2021). A colony of D. speciosa indicates that initiation of formation of the Numa coral bed in Chiba Prefecture dates back to 7.8 ka (Sato et al 1968).…”
Section: Resultsmentioning
confidence: 96%
“…Because of the sporadic distribution of marine terraces, RSL records are scattered on southern Shikoku Island. Other studies have identified pre-historical earthquake-related sediments on Shikoku Island (Iwai et al, 2004;Nanayama et al, 2020Nanayama et al, , 2021Shimada et al, 2019;Tanigawa et al, 2018). Iwai et al (2004) studied piston core sediments from off Cape Muroto and identified 31 seismoturbidite layers that may have been generated during earthquake events in the last 7000 years.…”
mentioning
confidence: 99%